International operations : how multiple environments impact productivity and location decisions - Steenhuis, Harm-Jan. (2014 digital library., 2015)
Provides a comprehensive discussion of the factors that affect international operations. International operations can involve sales and production activities. Companies are often too optimistic about the productivity of international sales, that is, overestimate the development of international markets. Companies are also often too optimistic about the productivity of international production, that is, underestimate the costs and efforts involved. This leads to disappointing results or divestment of international operations.